Adult volunteer retention in an after-school garden club setting : a case study - Huber, Erika (Kansas State University, 2011)
Once a fixture of American schoolyards during the early 1900’s, school gardens in the United States are again growing in popularity. It is estimated that one-fourth of all public and private schools in the U.S. have a school garden. Funding, teacher involvement, support of the principal, volunteer help, garden coordination, maintenance assistance and site availability are all factors found to contribute to the success of school gardens and are also found to be the barriers to sustainability of school gardens. Many of these challenges can be overcome with the support of volunteers. Little is known however, about individuals who volunteer their time to a school garden program and more importantly no research has investigated the specific variables influencing volunteer retention in an after-school garden club program setting. A case-study of long-term adult after-school garden club program volunteers was conducted to determine the variables affecting one’s decision to continue volunteering after one semester with a program of this type. Twenty long-term after-school garden club program volunteers were interviewed. Interview responses were grouped into main theme and subtheme categories using NVivo, a qualitative analysis software. Main themes that had responses from at least 95% of the volunteers participating in the case-study, were isolated for further analysis. The top five subthemes for each of these isolated main themes were assessed and four of these main themes were found to have similar top five subthemes. These subthemes and the long-term volunteer demographics were then used to determine the variables affecting volunteer retention in an after-school garden club setting. Age, marital status and level of education were all found to affect length of volunteer service. Organizational commitment, positive volunteer relations, organizational support, learning opportunities and the opportunity to work with children all contributed to the decision of after-school garden club program volunteers to continue volunteering after one semester of service. Furthermore, it can be concluded that these volunteers continued to volunteer because their initial motivations, expectations and/or needs were met through their participation in the program.
Keywords: After-school garden club volunteers; Volunteer retention; School garden; Volunteer motivations; Organizational commitment and support; Long-term volunteer; Horticulture (0471); Social Research (0344)